Hydrogen-assisted growth of one-dimensional tellurium nanoribbons with unprecedented high mobility - Xu, Manzhang (2023)
High-mobility van der Waals ambipolar semiconductors are promising in logic and reconfigurable circuits, integrated optoelectronic circuits, due to the excellent gate-controlled capability and effectively tunability of major charge carriers by electrostatic field. Controllable growth of high-quality ambipolar semiconductors with high mobility and stability is highly glamorous and indispensable for further research. Here, we demonstrate a straightforward space-confined chemical vapor deposition (CVD) method to synthesize high-quality quasi-one-dimensional (1D) tellurium (Te) nanoribbons (NRs). By introducing H2 into the gas flow, endothermic compound H2Te was generated from the reaction of liquid Te with H2, and consequently decomposed into elemental Te at low temperature. Further, the Te NRs have been utilized for in-situ fabrication of field-effect transistors (FETs) without transferring process. Ambipolar features are achieved using nickel (Ni) as an ohmic contact. More importantly, the mobilities of the Te NR transistor for hole/electron are as high as 1755/28.6 cm2V−1s−1 and 4024/278 cm2V−1s−1 at room temperature and under a temperature below 20 K, respectively. Our findings confirm the novel strategy for synthesizing 1D elemental semiconductors and their applications with ambipolar behaviors.